Islam Sasak : Wetu Telu Versus Waktu Lima - Wijayanti, Nur (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Sasak religion or more specifically Islam Sasak is a reflection of local or traditional religious struggles dealing with a universal world religion, in this case is Islam. Islam Sasak is basically also Islam, as if Javanese Islam, Malay Islam and so on. The original Sasak Islam is called Wetu Telu, a local Islamic type that blends with traditional values. Wetu Telu's teachings make custom as a base to think and behave and make nature as the subject that can organize, maintain and cultivate something else. This view arouses some actions that tend to mystic. While the teachings of Waktu Lima make the science of religion as a standard of thinking and behaving as well as viewing nature as subject-object. Nature is seen as a rational object, which can be exploited by man and rather than exploits the human beings, and at the same time become a sacred subject, so born a rational-mystical action.